Non-Invasive Analyses of Altered Schaedler Flora in C57Bl/6J and Balb/c Mice to Monitor Hygiene Status of a Housing Facility - Rebecca Nistelberger; Patrizia Gibler; Lisa Barones; Arno Absenger; Julia B. Kral-Pointner; Manuel Salzmann; Boris Hartmann; Bruno K. Podesser; Phillip J. Hohensinner; Roberto Plasenzotti (Animals)
The composition of the gut microbiome, defined by environmental factors, significantly affects research outcomes, with variations observed across animal facilities. Efforts to standardize led to the definition of the ‘Altered Schaedler flora’ (ASF), comprising eight bacterial groups. Our data highlights the variability of ASF under pathogen contact. Feces from two wild-type strains (C57Bl/6J and Balb/c mice) with and without proven infection was collected in two different animal facilities and analyzed. The data show a significant difference in the quantity (either reduction or increase) of the eight ASF bacterial groups when comparing infected and non-infected mice across different housing areas (SPF-specific pathogen-free, quarantine, and conventional-experimental areas) within a facility, as well as in comparison to another facility. Furthermore, strain-specific differences are also evident, with certain ASF groups showing a reduction in quantity at one facility but an increase at the other, comparing the same housing area. Comparative studies across facilities confirmed the necessity of baseline determination for accurate ASF analysis. Performing ASF analysis, facilitated by in-house qPCR (quantitative polymerase chain reaction) kits, offers prompt and precise microbiome profiling, enhancing experimental accuracy and health monitoring in animal research settings.